NEED FOR ORTHODONTIC TREATMENT AND SELF-PERCEPTION IN PATIENTS CHILDREN FACULTY OF DENTISTRY OF UNIVERSIDAD NACIONAL DEL NORDESTE - Olivera, Paola Berenice (2025)
Objective: to analyze the need for orthodontic treatment and its relationship with self-perception in children with mixed dentition patients of the Faculty of Dentistry of the National University of the Northeast. Materials and methods: A cross-sectional observational descriptive study was conducted. For the clinical examination, a fact sheet was presented to the parents and/or guardians of the procedures and objectives of the work signing an informed consent and assent by the patients to be evaluated. The clinical examination was carried out by a single examiner trained for this purpose. All selected patients were given an Orthodontic Treatment Need Index. The analysis of the data was done using the statistical software InfoStat version 2021. Results: 163 patients have been evaluated, 50% correspond to the female gender and 50% to the male sex. Patients were aged between 6 and 11 years, with an average of 7.5 years and a standard deviation of 1.32 years. The Independence test was performed by (χ2), we worked with a significance level p = 0.05. between the dental health component of the IOTN and self-perception of the dental aesthetics given by the Aesthetic component of the IOTN, where a correlation between both variables could not be determined. Conclusions: no relationship was found between the need for orthodontic treatment and self-perception in children with mixed dentition patients from the Faculty of Dentistry of the UNNE.